DEVELOPMENT OF EDUCATION AND TRAINING PROGRAM DPC SPN DNATURE IMPROVES HUMAN RESOURCES ON THE QUALITY OF JOB LIFE FOR TRADE UNION MEMBERS IN SERANG REGENCY COMPANIES - April Laksana; Asep Saepulloh (SEAN Institute, 2022)
There are many companies in Banten Province, with several companies with the most significant capital investment as an industrial head in modern Cikande in Serang regency. Each company has several Trade Unions housed in Serang Regency such as the National Workers Union (SPN), which has been established for a long time in Serang district. Workers are assets of companies where they are the most essential part of carrying out production activities in each company, workers are members of the Trade Unions who have a high dedication in protecting workers and their members in all the rights owned by workers in each company in the field of education, so that the quality of self possessed by workers becomes one capital to develop knowledge and performance in the company where they work. The Branch Representative Council (SPN) of Serang Regency has a development in the field of work programs in the National Trade Union, to be used as a work reference in providing welfare and quality of work life for the development of potential in the field of education and training for its members.